2020
DOI: 10.1038/s41467-020-15817-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial E-selectin inhibition improves acute myeloid leukaemia therapy by disrupting vascular niche-mediated chemoresistance

Abstract: The endothelial cell adhesion molecule E-selectin is a key component of the bone marrow hematopoietic stem cell (HSC) vascular niche regulating balance between HSC self-renewal and commitment. We now report in contrast, E-selectin directly triggers signaling pathways that promote malignant cell survival and regeneration. Using acute myeloid leukemia (AML) mouse models, we show AML blasts release inflammatory mediators that upregulate endothelial niche E-selectin expression. Alterations in cell-surface glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
136
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 57 publications
(79 reference statements)
12
136
0
Order By: Relevance
“…However, targeting the interaction between LSC and selectins on endothelial cells is an area of active research as upregulation of E-selectin on endothelial cells has been associated with LSC survival and chemotherapy resistance [ 20 , 111 ]. Inhibition of E-selectin with the small molecule GMI-1271 (uproleselan) in combination with chemotherapy has been shown to prolong survival in a mouse model of AML [ 21 ]. Mechanistically, Barbier et al showed in murine experiments using adoptive transfer of HSCs that had been retrovirally transduced with the human MLL-AF9 fusion oncogene that AML blasts exhibit an increased E-selectin-binding potential that enabled retention of AML blasts within the bone marrow and could contribute to chemotherapy resistance [ 21 ].…”
Section: Current and Novel Molecularly Targeted Therapies For Hypementioning
confidence: 99%
See 4 more Smart Citations
“…However, targeting the interaction between LSC and selectins on endothelial cells is an area of active research as upregulation of E-selectin on endothelial cells has been associated with LSC survival and chemotherapy resistance [ 20 , 111 ]. Inhibition of E-selectin with the small molecule GMI-1271 (uproleselan) in combination with chemotherapy has been shown to prolong survival in a mouse model of AML [ 21 ]. Mechanistically, Barbier et al showed in murine experiments using adoptive transfer of HSCs that had been retrovirally transduced with the human MLL-AF9 fusion oncogene that AML blasts exhibit an increased E-selectin-binding potential that enabled retention of AML blasts within the bone marrow and could contribute to chemotherapy resistance [ 21 ].…”
Section: Current and Novel Molecularly Targeted Therapies For Hypementioning
confidence: 99%
“…Inhibition of E-selectin with the small molecule GMI-1271 (uproleselan) in combination with chemotherapy has been shown to prolong survival in a mouse model of AML [ 21 ]. Mechanistically, Barbier et al showed in murine experiments using adoptive transfer of HSCs that had been retrovirally transduced with the human MLL-AF9 fusion oncogene that AML blasts exhibit an increased E-selectin-binding potential that enabled retention of AML blasts within the bone marrow and could contribute to chemotherapy resistance [ 21 ]. Furthermore, treatment with GMI-1271 increased mobilization of AML blasts from the bone marrow and sensitized them to the effects of cytarabine with a concurrent reduction in the number of LSCs resulting in a survival advantage compared to control mice [ 21 ].…”
Section: Current and Novel Molecularly Targeted Therapies For Hypementioning
confidence: 99%
See 3 more Smart Citations